IMPLEMENTASI MANAJEMEN MUTU TERPADU DI SDIT INSAN MANDIRI JAKARTA - KHOIRUNNISA KHOIRUNNISA (Jurnal Manajemen Pendidikan, 2014)
This thesis aims to evaluate the implementation of Total Quality Management (TQM), covering the customer satisfaction and continuous improvement at SDIT Insan Mandiri Jakarta. Evaluation is conducted by studying customer’s perception both internals and externals. This research applies qualitative approach with a case study method. The data were collected through observation, interview, and studying related documents and recordings This research starts from February until July 2013. The findings of the research are: overall, implementation of TQM has increase customer satisfaction and encourage continuous improvement at SDIT Insan Mandiri. Those TQM aspects work effectively since management of SDIT Insan Mandiri Jakarta implemented Total Quality Management.The findings lead to the recommendation that (1) The management should build more facilities to support learning activities to enhance customer satisfaction, (2) SDIT Insan Mandiri should conduct comparative studies to broaden their horizons and compare their advantages and disadvantages to other schools.